2000
DOI: 10.1074/jbc.275.19.14281
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Sphingosine 1-Phosphate Receptor, Edg-8

Abstract: Three G protein-coupled receptors (Edg-1, Edg-3, and Edg-5) for the lysolipid phosphoric acid mediator sphingosine 1-phosphate have been described by molecular cloning. Using a similar sequence that we found in the expressed sequence tag data base, we cloned and characterized of a fourth, high affinity, rat brain sphingosine 1-phosphate receptor, Edg-8. When HEK293T cells were co-transfected with Edg-8 and G protein DNAs, prepared membranes showed sphingosine 1-phosphate-dependent increases in [35 S]guanosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
219
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(230 citation statements)
references
References 28 publications
8
219
0
2
Order By: Relevance
“…As intercellular messengers lysosphingolipids act on speci®c receptors, some of which couple to pertussis toxin (PTX) sensitive G-proteins (Goetzl & An, 1998;Meyer zu Heringdorf et al, 1997). While some members of the Edg receptor family are preferentially activated by lysophosphatidic acid, Edg1, Edg3, Edg5, Edg6 and Edg 8 are preferentially activated by SPP (Im et al, 2000; renal function. In the present study we report that systemically infused SPP can alter renovascular and tubular function in anaesthetized rats in a PTX-sensitive manner, whereas SPPC, SPH and GLU alter tubular functions in the absence of detectable renovascular e ects.…”
Section: Introductionmentioning
confidence: 99%
“…As intercellular messengers lysosphingolipids act on speci®c receptors, some of which couple to pertussis toxin (PTX) sensitive G-proteins (Goetzl & An, 1998;Meyer zu Heringdorf et al, 1997). While some members of the Edg receptor family are preferentially activated by lysophosphatidic acid, Edg1, Edg3, Edg5, Edg6 and Edg 8 are preferentially activated by SPP (Im et al, 2000; renal function. In the present study we report that systemically infused SPP can alter renovascular and tubular function in anaesthetized rats in a PTX-sensitive manner, whereas SPPC, SPH and GLU alter tubular functions in the absence of detectable renovascular e ects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent identification of cell surface heptahelical receptors for S1P and its structurally related lysophospholipid, lysophosphatidic acid (LPA), which are collectively designated EDG (for endothelial differentiation gene) or LP (for lysophospholipid) receptors, strongly suggests that a diversity of S1P-induced responses are mediated through the EDG receptors (5,15,26,49,65,66,68), although some biological activities of S1P were reported to be mediated through its intracel-lular actions (16,54,57,58,65,66,70,74). Among the EDG receptors, EDG1, EDG3, EDG5 (AGR16 or H218), and EDG8 are identified as receptors specific for S1P (8,20,30,34,35,44,46,47,49,65,66,71), while EDG2, EDG4, and EDG7 are receptors specific for LPA (5,15,26,49). EDG1, EDG3, and EDG5 are widely expressed in various tissues (25,53,76), whereas expression of EDG8 is confined to the central nervous system (30).…”
mentioning
confidence: 99%
“…Among the EDG receptors, EDG1, EDG3, EDG5 (AGR16 or H218), and EDG8 are identified as receptors specific for S1P (8,20,30,34,35,44,46,47,49,65,66,71), while EDG2, EDG4, and EDG7 are receptors specific for LPA (5,15,26,49). EDG1, EDG3, and EDG5 are widely expressed in various tissues (25,53,76), whereas expression of EDG8 is confined to the central nervous system (30). We and others have shown that the S1P receptors exhibit distinct signaling characteristics.…”
mentioning
confidence: 99%
“…Although all these receptors are activated by S1P binding, studies with receptor inhibitors suggest variations in the S1P binding site among these receptors [152,158,159]. There are also differences in the coupling of receptor activation to downstream G proteins [160][161][162][163]. S1P 1 couples to G i , S1P 2 and S1P 3 couple to Gi, Gq, and G 13 .…”
Section: Overview Of S1p Family Of Receptorsmentioning
confidence: 99%